Neuromuscular responses at acute moderate and severe hypoxic exposure during fatiguing exercise of the biceps brachii - Jasmin R. Jenkins; Owen F. Salmon; Ethan C. Hill; Jason B. Boyle; Cory M. Smith (Current Research in Physiology, 2021)
Purpose: The present study examined acute normobaric hypoxic exposure on the number of repetitions to failure, electromyographic (EMG) repetition duration (Time), EMG root mean square (RMS) and EMG mean power frequency (MPF) during biceps brachii (BB) dynamic constant external resistance (DCER) exercise. Methods: Thirteen subjects performed two sets of fatiguing DCER arm curl repetitions to failure at 70% of their one repetition maximum under normoxic (NH), moderate hypoxia FiO2 = 15% (MH) and severe hypoxia FiO2 = 13% (SH). Electromyography of the BB was analyzed for EMG Time, EMG RMS, and EMG MPF. Repetitions were selected as 25%, 50%, 75%, and 100% of total repetitions (%Fail) completed. Pulse oximetry (SpO2) was measured pre-and post-fatigue. Results: There was no significant three-way (Condition x Set x %Fail) or two-way (Condition x Set) interaction for any variable. The number of repetitions to failure significantly decreased from (mean ± SEM) 18.2 ± 1.4 to 9.5 ± 1.0 with each Set. In addition, EMG Time increased (25% < 50%<75% < 100%), EMG RMS decreased (50% > 75%>100%), and EMG MPF decreased (75% > 100%) as a result of fatiguing exercise. SpO2 was lower during MH (Δ5.3%) and SH (Δ9.2%) compared to NH and as a result of fatiguing exercise increased only in MH (Δ2.1%) and SH (Δ5.7%). Conclusion: The changes in BB EMG variables indicated exercise caused myoelectric manifestations of fatigue, however, acute moderate or severe hypoxia had no additional influence on the rate of fatigue development or neuromuscular parameters.